PENINGKATAN HASIL BELAJAR TENTANG LUAS BANGUN MELALUI MODEL KOOPERATIF STAD DAN KUIS - Kiswargoto Kiswargoto (LPPM UNISDA, 2017)
The study aimed to prove and know (1) the learning of Cooperative Model STAD can improve the students in learning of Model Area be more spirit, (2) the playing of quiz can improve the students in learning of Model Area be more spirit. This classroom action research was done by three cycles. Each cycle consisted of planning, action, observation, and reflection. The subject was the sixth graders of the second state elementary school Kranji with 13 students. The data collection used the method of observation, questionnaires, written test, and activity, then documentation. The study result showed that there is the improvement of the achievement average followed by the the learning completeness. The first cycle achieved 61,67 and the students learning completeness achieved 58,33%, the second cycle achieved 70 and the students learning completeness achieved 69,23%, the third cycle achieved 75,38 and the students learning completeneass achieved 100%, because the learning completeness has achieved 100% with the score of 60->60, so the conducted target has achieved. Based on the result, it can be conclude that (1) the learning of Cooperative model STAD can improve the student in learning of Model Area be more spririt, improve the learning process, and the learning achievement. (2) the playing of Quiz can improve the students in learning of Model Area be more spirit, improve the learning process, and the learning achievement.